(untitled) (Economic studies journal, 2020)
The study aimed to clarify the relationship between exports and GDP during the period (2018-1970). The model is estimated depending on two variables namely current GDP as a dependent variable and total exports as an independent variable using a set of standard and statistical tools such as co-integration, Granger causality, and ECM error correction model utilised from the Eviews 10. The research proved that there is a short and long term equilibrium relationship between exports and GDP in Libya during the study period. There is two-way causal relationship between exports, GDP, and export growth leads to GDP growth.